(untitled) (Indonesian Theological Justice Review, 2024)
Indonesia has experienced significant religious and ethnic conflicts, particularly in regions such as Maluku and Central Sulawesi, leading to deep divisions within communities. This paper explores the role of theological education in promoting justice and reconciliation in post-conflict Indonesia. The study examines how theological institutions, particularly seminaries and Islamic boarding schools (pesantren), contribute to the healing process by teaching peacebuilding, restorative justice, and forgiveness. The research analyzes curricula that incorporate interfaith dialogue, human dignity, and conflict resolution, emphasizing theological perspectives on reconciliation, justice, and healing. Drawing from Christian and Islamic teachings on peace and forgiveness, the paper argues that theological education can play a vital role in restoring social cohesion and building bridges between divided communities. The paper also highlights the challenges faced by theological institutions in promoting reconciliation, such as entrenched sectarian views, political tensions, and religious intolerance. Recommendations include expanding theological curricula to include peacebuilding and conflict resolution, encouraging interfaith collaboration in educational settings, and fostering a culture of dialogue and mutual understanding. By nurturing leaders committed to peace and justice, theological education can be a powerful tool for post-conflict healing in Indonesia.